“SABAH” DALAM PERSPEKTIF HUKUM INTERNASIONAL: MILIK FILIPINA ATAU MALAYSIA? - Shahrullah, Rina Shahriyani (JURNAL ILMU BUDAYA, 2014)
This writing is an attempt to understand the Sabah case based on the perspective of InternationalLaw. The disputes over claims of certain areas among members of ASEAN seem to be continued.After the case of Sipadan dan Ligitan which involved Indonesia and Malaysi, followed by thecase of Batu Puteth (Pedra Branca) between Singapore and Malaysia, the case of Sabah betwenthe Philippines and Malaysia came to the surface. This issue has to be included as an importantagenda for ASEAN because ASEAN should play important role as a mediator to resolve disputesamong its members. Unfortunately, thus far ASEAN has not played signifinact role in resolvingthe Sipadan-Ligitan case and the Batu Puteh (Pedra Branca) case which led to the trial of thecases by the International Court of Justice. Has the Sabah case to be ended in ICJ?Keywords: Sabah, dispute, international law, ASEAN